(untitled) - Torng, H. C. (Reading, Mass., 1964)
Provides the knowledge and skills that are basic to all digital system design. Solid foundation of theory permits development of systematic design procedures. Presents classical methods, such as Karnaugh maps. Quine-McCluskey minimization. Mealy and Moore circuits, state-table minimization, hazard-free asynchronous designs, etc. This edition features design with MSI circuits, including PLA's, and register transfer (state machine) approaches to sequential system design.
Keywords: Lý thuyết chuyển mạch,Switching theory